Reinterpreting Presidential Educational Requirements in Indonesia: Constitutional Court Decision No. 87/PUU-XXIII/2025 from the Perspective of Siyasah Dusturiyah - Anissa Rizqi Syafitri; Bobang Noorisnan Pelita; Ridwan Eko Prasetyo (Journal of Indonesian Islamic Studies, 2026)
Constitutional Court Decision Number 87/PUU-XXIII/2025 concerning the minimum educational requirements for presidential and vice-presidential candidates has generated constitutional debate regarding the balance between democratic inclusiveness and leadership competency in Indonesia’s constitutional system. The decision rejected the petition seeking reinterpretation of Article 169 letter r of Law Number 7 of 2017 concerning General Elections, which requires candidates to possess at least a senior high school diploma or its equivalent. This study aims to analyze the juridical foundation of the Constitutional Court’s reasoning within the doctrine of open legal policy, examine its implications for constitutional loss and judicial review access, and evaluate the relevance of the minimum educational requirement from the perspective of siyasah dusturiyah. This research employs normative juridical methods with statute and conceptual approaches using constitutional regulations, court decisions, and Islamic political thought as primary analytical sources. The findings reveal that the Constitutional Court reaffirmed the doctrine of open legal policy and judicial restraint by emphasizing that the determination of educational qualifications for presidential candidates belongs to legislative authority as long as constitutional principles are preserved. The decision also strengthens the Court’s restrictive interpretation of constitutional loss by limiting judicial review access to applicants who can demonstrate direct constitutional injury. From the perspective of siyasah dusturiyah, however, the minimum educational requirement of senior high school graduation is considered substantively inadequate because it does not fully reflect the principle of kifayah ‘ilmiyyah emphasized by Al-Mawardi and may potentially undermine maslahah ‘ammah in contemporary governance. This study argues that leadership competency should be positioned as an important component of constitutional morality and public welfare within Indonesia’s constitutional democracy.